(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Garbhini Paricharya, or the care of a pregnant woman, is a vital aspect of Ayurvedic medicine that emphasizes the importance of holistic health during pregnancy. This traditional practice outlines guidelines for maternal care to ensure both the mother’s and the child’s well-being. The principles of Garbhini Paricharya highlight the interconnectedness of physical, mental, and emotional health, advocating for a nurturing environment during one of life’s most transformative periods. Adverse birth outcomes refer to negative results of pregnancy and childbirth, which can include preterm birth, low birth weight, stillbirth, and neonatal complications. Thus, the current review is based on the role of Garbhini Paricharya in the prevention of adverse birth outcomes.